2007
DOI: 10.4049/jimmunol.178.3.1268
|View full text |Cite
|
Sign up to set email alerts
|

Tolerization of Tumor-Specific T Cells Despite Efficient Initial Priming in a Primary Murine Model of Prostate Cancer

Abstract: In this report, we studied T cell responses to a prostate cancer Ag by adoptively transferring tumor Ag-specific T cells into prostate tumor-bearing mice. Our findings demonstrate that CD8+ T cells initially encountered tumor Ag in the lymph node and underwent an abortive proliferative response. Upon isolation from the tumor, the residual tumor-specific T cells were functionally tolerant of tumor Ag as measured by their inability to degranulate and secrete IFN-γ and granzyme B. We next sought to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…We show that unlike lower avidity TCR lo T cells, the higher avidity TCR hi T cells that persisted in the TME lost their ability to produce IFN-γ and to mobilize CD107a, hallmarks of tolerance. These data confirm our previous report demonstrating loss of CTL function among tumor-specific CD8 + T cells that infiltrate prostate tumors (21). Morgan and colleagues also reported that higher avidity, Flu-HA-specific T cells were more readily tolerized than lower avidity T cells with identical specificity (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We show that unlike lower avidity TCR lo T cells, the higher avidity TCR hi T cells that persisted in the TME lost their ability to produce IFN-γ and to mobilize CD107a, hallmarks of tolerance. These data confirm our previous report demonstrating loss of CTL function among tumor-specific CD8 + T cells that infiltrate prostate tumors (21). Morgan and colleagues also reported that higher avidity, Flu-HA-specific T cells were more readily tolerized than lower avidity T cells with identical specificity (22).…”
Section: Discussionsupporting
confidence: 93%
“…However, the failure of many patients to develop long-term tumor control may be, in part, due to tolerization of transferred T cells (18). Our lab has reported that in an experimental model of prostate cancer, tumor antigen-specific CD8 + T cells become tolerized after infiltrating tumor tissue (1921). One previous study suggested that recognition of a xenogeneic, tumor-associated antigen by higher avidity T cells leads to increased susceptibility to tolerization (22).…”
Section: Introductionmentioning
confidence: 99%
“…Many cancer vaccines that were specifically designed to induce strong tumor-specific T-cell responses are in development [45]. However, effector T cells can still be inactivated upon entering the immunosuppressive tumor microenvironment [46]. Pairing a cancer vaccine with NHS-IL12 treatment might allow for the vaccine-induced T cells to better infiltrate the tumor and remain active by virtue of their exposure to NHS-IL12.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prostate glands of patients with cancer contain a CD4 and CD8 T-cell infiltrate, phenotypic analyses of these cells 8,64,65 and numerous murine studies 6670 are consistent with the notion that these infiltrating cells are nonfunctional in lytic function. Several T-cell molecules seem to contribute to this lack of function, most notably CTLA4, which interacts with B7 family molecules on antigen-presenting cells to downregulate T-cell function.…”
Section: Immune Modulators (Brakes and Accelerators)mentioning
confidence: 56%